1999
DOI: 10.1055/s-0037-1614848
|View full text |Cite
|
Sign up to set email alerts
|

Haematological Abnormalities in Early Abstinent Alcoholics Are Closely Associated with Alterations in Thrombopoietin and Erythropoietin Serum Profiles

Abstract: SummaryNumerous reports exist on haematological pathology in alcoholism. However, no data are available regarding a potential involvement of haematopoietic growth factors in the recovery from alcohol-induced haematological abnormalities upon abstinence. Therefore, thrombopoietin (TPO) and erythropoietin (EPO) serum levels along with haematological and other routine laboratory parameters were closely followed in 14 thoroughly characterized male alcoholic patients over one to five months of controlled abstention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
2
5
0
3
Order By: Relevance
“…Indeed, there was evidence for iso-to hypo-osmolar hypervolemia in our patients, even after several months of abstinence. This concept is supported to some extent by the permanently decreased hematocrit and hemoglobin levels found in this and our previous study (Schmitt et al, 1999). A persistently increased mean corpuscular volume may also be somewhat related to this phenomenon (Hasselblatt et al, 2001).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Indeed, there was evidence for iso-to hypo-osmolar hypervolemia in our patients, even after several months of abstinence. This concept is supported to some extent by the permanently decreased hematocrit and hemoglobin levels found in this and our previous study (Schmitt et al, 1999). A persistently increased mean corpuscular volume may also be somewhat related to this phenomenon (Hasselblatt et al, 2001).…”
Section: Discussionsupporting
confidence: 82%
“…Most of these alterations are thought to be reversed within the first 2 to 4 weeks of abstinence. Few studies give hints that there might be persistent alterations even after months of abstinence (Adinoff et al, 1990;Ehrenreich et al, 1997c;Harding et al, 1996;Hasselblatt et al, 2001;Ogata, 1963;Schmitt et al, 1999).…”
mentioning
confidence: 99%
“…Recent data have indicated a direct role for ethanol and its metabolites, as evidenced by the generation of ethanol-and acetaldehyde-derived structural modifications in erythrocyte constituents in heavily drinking subjects (Gaines et al, 1979;Latvala et al, 2001;Niemelä and Israel, 1992;Peterson et al, 1988;Stevens et al, 1981) and by the suppression of hematopoietic progenitor cell proliferation by ethanol and acetaldehyde (Levine et al, 1986;Meagher et al, 1982). A cytotoxic effect of ethanol on erythropoiesis is supported by the occurrence of erythroblast vacuolization, as seen here in 24% of the alcoholabusing patients and by previous evidence showing that after heavy alcohol intake, abstinence is usually followed by reticulocytosis (Schmitt et al, 1999). Previous in vitro studies have shown that ethanol and acetaldehyde inhibit colony formation by committed stem cells and that the erythroid cells are particularly vulnerable (Meagher et al, 1982).…”
Section: Discussionsupporting
confidence: 73%
“…Interestingly, the anemic patients also showed granulocytopenia significantly more often, suggesting a generalized ethanol-induced marrow suppression. It is possible that there are close interactions between the different bone marrow cell lines in responding to ethanol toxicity, because previously, thrombopoietin and erythropoietin serum profiles were also shown to be closely associated in alcoholics (Schmitt et al, 1999). When ethanol is withdrawn, the platelet counts return from low to normal or supernormal levels (rebound thrombocytosis) in 1 to 3 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…CD4 count and HIV VL are altered by non-adherence to antiretroviral therapy which is strongly associated with alcohol use (Braithwaite and Bryant, 2010; Braithwaite et al, 2008). Hemoglobin, platelets, aspartate transaminase and alanine transaminase are altered by direct toxicity of alcohol and by non-adherence to antiretroviral treatment (Anderson et al, 2014; Conigliaro et al, 2003; Lo et al, 2014; Schmitt et al, 1999; Sullivan et al, 2008). Given this dual effect of alcohol among HIV+ individuals, we might expect the VACS Index to be sensitive to adverse health effects from increasing alcohol exposure in this population and that is what we observed.…”
Section: Discussionmentioning
confidence: 99%